The project-state and its rivals a new history of the twentieth and twenty-first centuries - Maier, Charles S. (London Harvard University Press, 2023)
Charles Maier offers a new narrative of the long twentieth century, focused on institutions that shaped politics and societies: project-states, driven by democratic or authoritarian ideologies; capital; and advocates of apolitical values, such as health, human rights, and international law. In this we discern the unfolding of our own troubled time
Includes bibliographical references and index.
Keywords: Twentieth century